X-ray magnetic circular dichroism in d and f ferromagnetic materials: recent theoretical progress. Part I (Review Article): - Antonov, V.N.; Shpak, A.P.; Yaresko, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The current status of theoretical understanding of the x-ray magnetic circular dichroism (XMCD) of 3d compounds is reviewed. Energy band theory based upon the local spin-density approximation (LSDA) describes the XMCD spectra of transition metal compounds reasonably well. Examples which we examine in detail are XPt3 compounds (with X = V, Cr, Mn, Fe, Co, and Ni) in the AuCu3 structure, Heusler compounds Co2MnGe, Co2NbSn, and compounds with noncollinear magnetic structure IrMnAl and Mn3ZnC. Recently achieved improvements for describing the electronic and magnetic structures of 3d compounds are discussed.